Code-switching of English-French in French Kissing Novel by Catherine Sanderson - Roslan, Amirah Syazwani; Hassan @ Hussin, Omrah (Human Resource Management Academic Research Society, 2021)
The tremendous development of today’s globalization has resulted in the employment of code-switching which was perceived as the usage of more than one language in a particular discourse among individuals. Consequently, the trends of applying multiple languages in a written context especially in novels are seen to be increasing over years. Apart for leisure purposes, novels also allowed us to discover varied language phenomenon including code-switching due to its non-specific writing styles. This study investigated code-switching of English-French used in the narrative and dialogues of the French Kissing novel by Catherine Sanderson. Simultaneously, through a descriptive qualitative method, code-switching analysed in the novel was distributed, analyzed and described accordingly. Firstly, this study applied a theoretical framework pioneered by Poplack (1980) namely tag code-switching, intrasentential code-switching and intersentential code-switching. The results of the initial review found that intrasentential code-switching has the highest frequency (79.34%), followed by intersentential code-switching (13.64%) and tag code-switching (7.02%). Moreover, this study also coded the factors influencing code-switching in the novel according to Holmes (2008). The findings demonstrated that the three highest factors contributing to code-switching are switching for effective function, topic as well as participants, solidarity and status. Meanwhile, lexical borrowing and metaphorical switching were the least factors of the code-switching phenomenon in the novel. Generally, the findings explained code-switching as an effective communicative strategy which are beneficial to make the novelist’ intended meaning explicit and to preserve the engagement among the characters. Besides, code-switching has occasionally remarked the discourse practiced among the local society in France. Finally, further studies are suggested to be explored in depth through other written media precisely, novels under different perspectives.